Genetic Analysis of PICK1 Gene in Alzheimer's Disease: A Study for Finding a New Gene Target - Xu, Lingjia; Chen, Yanxing; Shen, Ting; Lin, Caixiu; Zhang, Baorong (Frontiers in Neurology, 2019)
Abstract Background Alzheimer's disease (AD) is a neurodegenerative disease with no effective treatment. Researchers have focused on exploring biomarkers for its early diagnosis, especially on finding a new gene target. Recent studies have shown that protein interacting with C-kinase-1(PICK1) is related to AD through regulating hippocampal synaptic plasticity. PICK1 gene polymorphisms have been identified in psychological and other related disorders. Methods This study included 133 sporadic AD patients and 173 healthy controls. All coding exons and intron-exon boundaries of the PICK1 gene were ampliﬁed by polymerase chain reaction, which were subsequently sequenced and analyzed. Results This is the first genetic association study to investigate the association between PICK1 gene and AD risk in Chinese Han population. Seven single nucleotide polymorphisms (SNPs) were found in our research (rs397780637, rs713729, rs2076369, rs58230476, rs7289911, rs149474436; and rs146770324 for patient M1659 only). Frequencies of the T allele (p = 0.002; OR, 0.083; 95%CI, 0.011-0.634) and TT/TC genotypes (p = 0.001) of rs149474436 were lower in AD patients than in the controls. The GG homozygotes of rs397780637 were found to be associated with an increased risk of AD (p = 0.018) in APOEε4 allele carriers, while the frequency of the T allele of rs149474436 was significantly lower among AD patients in APOEε4 non-carriers (p = 0.005). Conclusions Our results suggest that PICK1 gene SNPs are associated with AD susceptibility in East Asian population, T allele of rs149474436 may play as a protective factor while the rs397780637 GG homozygotes may be associated with an increased risk of AD. Further studies should be considered in a larger cohort of patients with diverse demographics.